Determination of peculiarities of analysis of integration risks in projects of creation of transport and logistics centers - Kovtun, Tetiana; Smokova, Tetiana; Smrkovska, Victoriya (Technology audit and production reserves, 2020)
The object of research is the risk of tearing of integration ties between the participants arising in the projects of creation of transport and logistics centers. The specific features of the concept of "integration project risks" are defined, which include the risks that may affect the integration in the project and lead to disruption of the project as a system by breaking the integration links between its participants. One of the most problematic places is to identify integration risks in the pre-investment phase of the project, in the process of qualitative and quantitative risk analysis. However, integration risks are hardly taken into account when designing transport and logistics centers. Particular attention is paid to logistical and project risks. Integration risks combine the features of both logistics and project risks and can lead to negative consequences for a logistics project. The study used qualitative risk analysis methods, namely Pareto analysis and ABC analysis, which allowed the project participants to be divided into groups with large, medium and low integration ties. Taking into account the number of transactions performed between the participants made it possible to determine the power of integration links. The combination of the results of the ABC analysis and the determination of the integration capacity is the basis for the creation of a matrix of integration potential of the project participants. In the course of the work, a qualitative risk analysis was carried out according to the proposed sequence of the project of creating a transport and logistics center. The use of quality management tools and the integration potential matrix developed by the authors made it possible to identify the many project participants who have the greatest impact on project integration. The use of the proposed approach to qualitative risk analysis of the integration gap between project participants at the beginning of the project will allow the identification of participants with high integration potential. extremely negative consequences.